2022
DOI: 10.1007/s11606-022-07721-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Physician Practices, Attitudes, and Knowledge Regarding Recombinant Zoster Vaccine

Abstract: Background Herpes zoster vaccination rates remain low despite longstanding national recommendations to vaccinate immunocompetent adults aged ≥ 50 years. The Advisory Committee on Immunization Practice (ACIP) updated its recommendations for recombinant zoster vaccine (RZV) in October 2021 to include immunocompromised adults aged ≥19 years. Objective To assess practices, attitudes, and knowledge about RZV, barriers to recommending RZV, and likelihood of recommending RZV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…Barriers to shingles vaccination among study participants included participant's perception that they were not at risk of getting shingles (33%). In about 27.5% of participants, the barrier was concerned about the vaccine's side effects, this was different from the findings mentioned in one parallel study in which the main barriers were found to be the cost and availability [20].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Barriers to shingles vaccination among study participants included participant's perception that they were not at risk of getting shingles (33%). In about 27.5% of participants, the barrier was concerned about the vaccine's side effects, this was different from the findings mentioned in one parallel study in which the main barriers were found to be the cost and availability [20].…”
Section: Discussioncontrasting
confidence: 82%
“…Assessing KAP regarding HZ vaccination is significant as the role of the doctor in knowledge distribution and patient's awareness depends on the level of awareness of the doctor. In addition, knowledge about shingles vaccine is important in certain situations in which any particular patient should be advised to get a shingles vaccination shot or not [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing first-dose coverage had a large impact on the potential public health impact of RZV. Research has shown that barriers to HZ vaccination include vaccine distrust [ 53 ], cost concerns [ 54 , 55 ], and low perceived risk [ 55 ]. However, uptake and/or completion could potentially be improved by provider education [ 56 , 57 ], physician’s recommendations [ 55 ], nurse/pharmacy administration [ 56 ], and use of prompts/reminders [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies among gastro-enterologists and rheumatologists in the USA and Canada with a similar design also reported a lack of consensus on who is responsible for identifying and administering vaccinations, as well as a lack of knowledge [ 25 , 26 , 27 , 28 ]. Other frequently reported barriers are lack of reimbursement, lack of priority, and lack of time [ 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%